LOOKING INTO THE EFL STUDENTS TYPE OF FEEDBACKS ON PEER CORRECTION ACTIVITY - Yunisrina Qismullah Yusuf; Tengku Maya Silviyanti; Rita Tauhidah (Soegijapranata Catholic University, 2016)
This research studies the types of feedbacks made by EFL students in a writing class. A number of 25 students essays were collected and analysed. The results revealed that a number of 61 responding feedbacks were found in the types of support, sharing knowledge, negotiation, appreciation and criticism. Meanwhile, 142 correcting feedbacks were found in the types of coded, uncoded, a combination of coded and uncoded and direct answer. The type most used in responding feedback was support, which indicates that it is an important pursuit in these students learning to drive each other into improving their writing skills with confidence. Whilst the least used was criticism, and this indicates that it was not considerably favoured to be given in the peer correction feedbacks since they restrain encouragement and cause social anxiety. The type most used in correcting feedbacks was a combination of coded and uncoded. This signifies that to provide both mark and symbol on an error can avoid confusion between the student corrector and the student writer. The least used was direct answer, which signified that it was only done by students who had high English proficiency and confidence to provide the correct answer directly on the errors.